Anxiety, depression, and sleep disturbances among people on long-term efavirenz-based treatment for HIV: a cross-sectional study in Beijing, China - Jing Xiao; Ying Liu; Bei Li; Leidan Zhang; Junyan Han; Hongxin Zhao (BMC Psychiatry, 2022)
Abstract Background Efavirenz (EFV)-induced neuropsychiatric toxicity bothers people living with HIV (PLHIV). Neuropsychiatric adverse effects of EFV may differ by length of time on EFV-based antiretroviral treatment (ART). Methods A cross-sectional, single-center study was conducted at Beijing Ditan Hospital in China from June–August 2020 among ART-experienced PLHIV who were on long-term EFV-based ART. 424 eligible virological suppressed participants were enrolled and divided into four groups according to time on EFV-based ART: group A (0.5 ≤ ART < 2 year), B (2 ≤ ART < 4 year), C (4 ≤ ART < 6 year), and D (ART ≥ 6 year). The questionnaires about 12-item Short Form Health Survey (SF-12), Hospital Anxiety and Depression Scale (HADS) and Pittsburgh Sleep Quality Index (PSQI) were administered to assess neuropsychiatric adverse events of EFV among different groups. Results Overall mental component summary scores (MCS) of SF-12 in PLHIV was 50.2, which was lower than general population. Overall prevalence of anxiety, depression and sleep disturbances was 15.6%, 15.3% and 58%, respectively. Prevalence of anxiety, depression and sleep disturbances did not vary significantly between the time-on-ART groups. Anxiety, depression, sleep disturbances had no correlation with time on EFV-based ART or CD4+ T cells counts. Conclusions In ART-experienced PLHIV in China, neuropsychiatric adverse events exist persistently and prevalence do not significantly change with prolonged time on EFV-based ART. The prevalence of sleep disturbances was high, suggesting that clinicians should pay more attention to long-standing psychiatric health to perform early and effective interventions.